Protection of Network Devices and Data security using Firewall: A literature Survey - Deshmukh, Gayatri; Kamble, Rachana; Solanki, Pratap Singh (International Journal of Computer Sciences and Engineering, 2021)
Firewalls play important role in any organization today. Firewall is a layer of security between organization Network and the Internet. A Firewall is programmed with security rules that prevent unregulated access to your internal Network. The rules might control employee access to websites and also prevent files leaving the company over Network. Any number of rules can be used to protect the data. In this literature survey, we studied the work carried out by various researchers about the protection of Network and data security.